2018
DOI: 10.1101/260364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vasohibin1, a new IRES trans-acting factor for induction of (lymph)angiogenic factors in early hypoxia

Abstract: Hypoxia, a major inducer of angiogenesis, is known to trigger major changes of gene expression at the transcriptional level. Furthermore, global protein synthesis is blocked while internal ribosome entry sites (IRES) allow specific mRNAs to be translated. Here we report the transcriptome and translatome signatures of (lymph)angiogenic genes in hypoxic HL-1 cardiomyocytes: most genes are not induced at the transcriptome-, but at the translatome level, including all IRES-containing mRNAs. Our data reveal sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…This problem has been circumvented by using another reporter gene such as beta-galactosidase [52]. Mutating the cryptic splicing sites in the LucR gene is also a good solution [72]. Stringent and carefully controlled experiments such as Northern blots, RT qPCR or first cistron knockdown have been necessary to demonstrate the presence of bona fide cellular IRESs [49,51,53,58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem has been circumvented by using another reporter gene such as beta-galactosidase [52]. Mutating the cryptic splicing sites in the LucR gene is also a good solution [72]. Stringent and carefully controlled experiments such as Northern blots, RT qPCR or first cistron knockdown have been necessary to demonstrate the presence of bona fide cellular IRESs [49,51,53,58].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, chronic heart failure is a public health issue. IRES-dependent translation plays a major role during ischemia: a very recent mid-scale study shows that, unexpectedly, the expression of most (lymph)angiogenic factors is not induced at the transcriptome level but at the translatome level in hypoxic cardiomyocytes [72]. The same study indicates that the IRESs of (lymph)angiogenic factors mRNAs, FGF1, FGF2, VEFGA, VEGFC and VEGFD are activated in early hypoxia, while non angiogenic IRESs such as EMCV or c- myc IRES are activated in late hypoxia.…”
Section: Ires-dependent Translation a Pivotal Mechanism In The Stmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypoxia also constitutes major stress in other pathologies, such as ischemic pathologies, in which artery occlusion leads to hypoxic conditions, and then angiogenesis is promoted as a cellular response to fight the lack of oxygen and nutrients in cells. It has been shown that (lymph)angiogenesis is also induced by hypoxia and mediated at both transcriptional and post-transcriptional levels [ 90 , 91 ]. VEGF-A and FGF2, major angiogenic factors, and the lymphangiogenic growth factor VEGF-C are all induced by hypoxia through a translational mechanism [ 90 ].…”
Section: Ires-dependent Translation Dysregulation-related Diseasesmentioning
confidence: 99%
“…VEGF-A and FGF2, major angiogenic factors, and the lymphangiogenic growth factor VEGF-C are all induced by hypoxia through a translational mechanism [ 90 ]. As we have already mentioned above, several IRESs have been identified in the mRNAs of (lymph)angiogenic growth factors from the FGF and VEGF families, suggesting that the activation of angiogenesis and lymphangiogenesis during stress might be highly controlled via IRES-mediated translation [ 91 ]. VEGF-A has pro-lymphangiogenic properties and its induction under hypoxia occurs in both physiological states and pathological conditions, such as ischemia or tumour development [ 92 ].…”
Section: Ires-dependent Translation Dysregulation-related Diseasesmentioning
confidence: 99%